Does more investment in primary care improve health system performance?. Issue 6 (June 2021) - van Gool, Kees; Mu, Chunzhou; Hall, Jane
Abstract: This study examines the association between primary care investment and performance, in 34 OECD countries for 2005–15. Specifically, we explore whether an increasing investment in primary care is associated with improved performance, and whether particular characteristics of organisation and delivery are associated with a better return on primary care investment. We take advantage of new data sources that provide rich information on health and health systems as well as economic and distributional characteristics. Multilevel modelling was utilised to analyse cross-country variation. The results show that greater investment in primary care does not improve health system performance for complex targets (i.e., no reduction in preventable hospital admissions) though there is modest improvement in breast and cervical cancer screening rates. We also found that those countries in which GPs are more aware of health promotion/preventive activities achieve higher screening rates with the same amount of investment. The findings imply that primary care investment strategies need to look beyond high-level expenditure and characteristics of primary care strength, to institutional and funding arrangements and how these link to policy goals. Despite broad enthusiasm for strengthening primary care in general, we conclude that primary care policy needs to be appropriately targeted to improve health system performance.